Medicine at a glance - Davey, Patrick (At a glance, 2006)
Medicine at a Glance provides a concise and accessible introduction and guide to the core curriculum for medical students. Following the familiar easy-to-use at a Glance format, each topic is presented as a double-page spread with key facts accompanied by clear tables, illustrations and diagrams encapsulating all the students need to know. This new edition of Medicine at a Glance: Is fully revised and updated - THE essential purchase for medical students. Has a unique structure, divided into over 65 clinical presentations and 150 common diseases. Covers the essential facts for the diagnosis and treatment of common symptoms and conditions. Includes 7 new chapters, dealing with topics such as: How to recognise the critically ill patient. Painless loss of vision / blindnes. Allergic reaction. Imaging in respiratory disease. Imaging in gastrointestinal disease. Presents diagrams and illustrations on the left and concise explanations on the right, providing a user-friendly overview of Medicine.